TINJAUAN PUTUSAN DI LUAR SURAT DAKWAAN TERHADAP PERKARA TINDAK PIDANA NARKOTIKA DAN PENGABAIAN SEMA NOMOR 1 TAHUN 2017 - Prasetya, Yuan Angger; Aldyan, Arsyad (Verstek, 2023)
This research aims to find out the reasons for the judge’s decision outside the indictment against a narcotics crime case associated with the theories in the Criminal Procedure Code and also SEMA Nomor 1 Tahun 2017. This research was conducted using doctrinal or normative legal research methods that are perspective or applied by using primary and secondary legal sources which are certainly related to the topic. The collection of legal materials by means of a literature study and using a statutory approach and a conceptual approach with a deductive syllogism so that it can be found whether the judge can decide on a case of narcotics crime outside the indictment. Keywords: indictment, judge decision, narcotics crime case.